A Benzochalcone Derivative, (E)-1-(2-hydroxy-6-methoxyphenyl)-3-(naphthalen-2-yl)prop-2-en-1-one (DK-512), Inhibits Tumor Invasion through Inhibition of the TNFα-Induced NF-κB/MMP-9 Axis in MDA-MB-231 Breast Cancer Cells - Soon Young Shin; Chang Gun Kim; Seunghyun Ahn; You Jung Jung; Dongsoo Koh; Young Han Lee; Yoongho Lim (Journal of Chemistry)
Tumor invasion is a critical step in tumor metastasis. In this study, we synthesized a novel benzochalcone derivative, (E)-1-(2-hydroxy-6-methoxyphenyl)-3-(naphthalen-2-yl) prop-2-en-1-one (DK-512), and characterized its effects on tumor invasion and its mechanism of action. We found that DK-512 strongly inhibited invasion of metastatic MDA-MB-231 breast cancer cells as revealed by a three-dimensional spheroid culture system. Tumor invasion and metastasis require disruption of the extracellular matrix. Matrix metalloproteinase-9 (MMP-9) is an endopeptidase that degrades extracellular matrix components. DK-512 significantly reduced tumor necrosis factor-α- (TNFα-) induced MMP-9 mRNA expression through the inhibition of RelA nuclear factor- (NF-) κB transcription factor. As our study was assessed in vitro, further works about in vivo efficacy of DK-512 are needed to gain further insights into whether DK-512 could be utilized as a scaffold for the development of antimetastatic agents for breast cancer.